Unemployment with Observable Aggregate Shocks - Grossman, Sanford J.; Hart, Oliver D.; Maskin, Eric S. (Journal of Political Economy, 1983)
A general equilibrium model of optimal employment contracts is developed where firms have better information about labor's marginal product than workers. It is optimal for the wage to be tied to the level of employment, to prevent the firm from falsely stating that the marginal product is low and cutting the wage. It is shown that an observed aggregate shock that leads to an interindustry shift in labor demand and that would have no effect on total employment under symmetric information leads to a reduction in employment when firms and workers have asymmetric information.